2022
DOI: 10.25000/acem.1076456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on night eating syndrome: A retrospective study

Abstract: Aim: Prevalence of night eating syndrome (NES) is higher in obese people. The effect of bariatric surgery on preoperative and postoperative eating disorders of obese patients remains controversial. This study aims to determine the preoperative and postoperative NES in patients who underwent bariatric surgery and the impact of surgery on this syndrome. Methods: The study was conducted on 29 patients who applied for bariatric surgery at a university hospital to treat morbid obesity. The questionnaire used as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the flood study, it was observed that 27.6% of the patients experienced NES preoperatively and 10.3% postoperatively. 21 Chang's 22 systematic review _ pass found the rate of NES after surgery to be between 1.9% and 42%. In a study by Ünal et al 23 those who experience weight regain after bariatric surgeries and those who do not compared to night eating was significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…In the flood study, it was observed that 27.6% of the patients experienced NES preoperatively and 10.3% postoperatively. 21 Chang's 22 systematic review _ pass found the rate of NES after surgery to be between 1.9% and 42%. In a study by Ünal et al 23 those who experience weight regain after bariatric surgeries and those who do not compared to night eating was significantly higher.…”
Section: Resultsmentioning
confidence: 99%